Characterizing candidate decompression rates for hypobaric hypoxic stunning of pigs. Part 1: Reflexive behavior and physiological responses - Martin, Jessica E.; Baxter, Emma M.; Clarkson, Jasmine M.; Farish, Marianne; Clutton, Richard E.; Greenhalgh, Stephen N.; Gregson, Rachael; McKeegan, Dorothy E. F. (Frontiers in Veterinary Science, 2022)
Alternatives to carbon dioxide (CO2) stunning for the commercial slaughter of pigs are urgently needed because there is robust evidence that exposing pigs to hypercapnic environments is associated with pain, fear and distress. Hypobaric hypoxia (via gradual decompression, also known as Low Atmospheric Pressure Stunning or LAPS) has been validated in poultry as a humane option, but its potential to improve the welfare of pigs at slaughter is unknown. We investigated the potential of hypobaric hypoxia to reliably elicit a non-recovery state in anaesthetized weaner-grower pigs within a commercially viable timeframe. We determined the effect of candidate decompression rates (40ms-1, 60ms-1, 80ms-1, 100ms-1, at two cycle durations 480s and 720s) on a range of physiological and reflexive behavioral indicators of hypoxia and death. We found the decompression rates tested caused a 100% death rate. As expected, decompression rate had overarching effects on behavioral and physiological markers of hypoxia and death, with faster decompression rates resulting in shorter latencies to cardiac arrest and cessation of breathing. We observed a higher proportion of pigs displaying repeated and prolonged whole-body movements (likely indicative of convulsive activity) at higher frequencies when we applied the slowest decompression rate (40ms-1) compared to all other rates. Since these responses may impact on carcass and meat quality, the slower rate of decompression (40ms-1) should be excluded as a candidate decompression rate. Furthermore, given marginal effects of decompression rate on physiological indicators of death and reflexive behavioral parameters, we also recommend that the fastest rate tested (100ms-1) is excluded in further study on conscious pigs (to prevent conscious animals being exposed to unnecessarily faster decompression rates which may compromise animal welfare). This work represents a necessary proof of principle step and confirms the potential of gradual decompression for stunning purposes in pigs. Importantly however, the data presented provide no information on the welfare outcomes associated with decompression in conscious pigs. Subsequent work should focus on comprehensive welfare assessment of intermediate decompression rates to determine the potential of hypobaric hypoxia to provide a humane stunning method for pigs.